Analisis Spasial Determinan Kejadian Berat Bayi Lahir Rendah (BBLR) di Provinsi Jawa Barat - Rahmi, Siti Aisyah; Utari, Diah Mulyawati; Arsyi, Miftahul; Munih, Munih (Jurnal Ilmiah Kebidanan Indonesia, 2023)
West Java Province is one of the provinces with LBW cases higher than LBW cases nationally due to behavior during pregnancy, access to health and spatial aspects. This study aim to analyze the spatial determinants of LBW incidence. Moran's Index Method globally and Local Indicators of Spatial Association (LISA) locally with the Geoda program in the 2018 West Java Province Riskesdas Report consisting of 18 districts and 9 cities. Globally, blood supplement tablet coverage has a positive spatial relationship with the incidence of LBW. Locally, there is a positive (High-high and Low-low) and negative (High-low and Low-high) spatial relationship on the coverage of blood supplement tablets, the coverage of ANC K4 visits, the proportion of very difficult access to health services (Puskesmas/Pustu/Pusling/ village midwives), the proportion of very difficult access to hospitals, the number of midwives and the number of available health facilities. In regencies/cities that have positive spatial relationships various interventions are needed to reduce negative spatial influences